Corruption, Country Governance And Firms’ Entry Mode: Evidence From Indonesia - Paras Dita; Ancella A. Hermawan (Green Publisher Indonesia, 2024)
Globalization and foreign direct investment (FDI) have made host country corruption a critical consideration for firms expanding internationally. This study investigates how perceived host country corruption influences the market entry mode choices of 207 Indonesian firms across 25 host countries between 2012-2022. Utilizing logistic regression analysis and grounded in transaction cost theory, we examine the likelihood of firms selecting joint ventures (JV) over wholly owned subsidiaries (WOS) in response to corruption risk. Results indicate that higher levels of perceived corruption in the host country significantly increase the probability of firms opting for JVs as a risk mitigation strategy. While strong country governance is often assumed to deter corruption, our findings suggest that it may not significantly reduce the perceived risk for firms entering foreign markets. This has important implications for policymakers seeking to attract foreign investment and for businesses developing strategies to navigate corrupt environments.